THE EFFECT OF TRAINING AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. INDOTRADE SEKAWAN S COMMITMENT - Misrofingah, Misrofingah; Riyanto, Arif (Journal of Research in Construction, Communication, and Commercial, 2022)
In the era of globalization that is currently developing and economicgrowth and development of the business world requires all companies to obtain maximum profits. For the sake of the survival of the company and so that the company's goals can be achieved, a management is needed that can manage everything related to the company's activities so that it isbetter. One of the decisions that must be taken by management is the management of human resources. Technology continues to develop, Human Resources, are required to be able to apply technology that is alsogrowing.